THE CONCEPT OF FORMING A RISK MANAGEMENT SYSTEM IN THE INNOVATIVE ACTIVITY OF A LOGISTICS AND TRANSPORT ENTERPRISE - TVORONOVYCH, Viktoriia; BOZHYDAI, Iryna; USTILOVSKA, Anastasiia; KAPITAN, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers the risk management system with indication of the key subsystems: a management entity, which includes a special group of people who carry out purposeful functioning of the management object using various methods and techniques of influence management; a management object, which includes risk, risky investments of capital and economic relations between entities in the course of entrepreneurial activity; a management process, which consists in the process of influence of the entity on the management object and can be carried out provided that certain information is circulated between the management and the management. The author also identifies certain functions performed by the above risk management subsystems. A number of tasks of risk management of a logistics and transport enterprise have been identified. Risk management should facilitate the implementation of measures aimed at achieving key performance indicators and improving the efficiency of the logistics and transport enterprise’s processes. It is noted that the functioning of any enterprise, in particular, a logistics and transport enterprise, depends on the built-up internal control system (ICS). To build an ICS of a logistics and transport enterprise, it is proposed to choose a model of three lines of protection. The traditional model of the three lines of defence involves the following division of functions: the first line includes operational management and is responsible for assessing, controlling and mitigating risks through effective internal controls; the second line provides risk management, identifies target risks, reports to senior management and monitors compliance; and the third line, which represents risk-based internal audit, reviews the implementation of risk management in the previous two lines and reports to senior management and the board on the effectiveness of risk assessment and management in the organisation. According to the adapted model, the first line includes business owners, shareholders, participants and senior management, who are empowered to make key decisions on approving and managing corporate strategy, including risk management strategy. They approve and direct the internal control system. It is noted that certain risks associated with innovation activities can be insured, such risks include: direct property losses associated with transportation, equipment operation, and supply of materials; indirect losses caused by dismantling and moving damaged property; risks subject to compulsory insurance (against industrial accidents, diseases, property damage, and vehicle theft).